Clinical outcomes in patients receiving edoxaban or phenprocoumon for prevention of stroke in atrial fibrillation: a German real-world cohort study - Christopher Hohmann; Magnus Lutz; Sheila Vignali; Kathrin Borchert; Karolin Seidel; Sebastian Braun; Stephan Baldus; Michael Näbauer (Thrombosis Journal, 2022)
Abstract Background Appropriate and timely anticoagulant therapy with vitamin K antagonists (VKAs) or non-vitamin K oral antagonists (NOACs) is essential for stroke prevention in non-valvular atrial fibrillation (NVAF). Comparative data regarding effectiveness and safety for edoxaban vs phenprocoumon, the predominant VKA in Germany, are scarce. Objectives The study evaluates effectiveness and safety of edoxaban vs phenprocoumon in NVAF patients in a German real-world setting. Methods German statutory health insurance claims data of the Institute for Applied Health Research Berlin (InGef) Research Database from 2014 until 2019 were analyzed. In NVAF patients, new users of edoxaban and phenprocoumon were compared to assess effectiveness (stroke/systemic embolism (SE)) and safety (bleeding) during therapy. Hazard ratios (HR) were estimated through multiple outcome-specific cox proportional hazard models adjusting for baseline characteristics. Outcomes of geriatric patients were analyzed in subgroup analyses. Results Between 2015 and 2018, 7,975 and 13,319 NVAF patients newly initiated treatment with edoxaban or phenprocoumon. After adjusting for baseline confounders, the risk of stroke/SE (HR: 0.85, 95% CI: 0.70–1.02) was numerically but not significantly lower, while the risk of major bleeding (HR: 0.69, 95% CI: 0.58–0.81) was significantly lower for edoxaban. In the geriatric subgroups, homogenous results compared to the main analysis were obtained. Conclusion The results of this real-world analysis indicated better effectiveness and safety outcomes in patients with NVAF initiating edoxaban treatment compared to phenprocoumon. The findings confirm that the beneficial effects observed in the pivotal ENGAGE AF-TMI 48 trial can also be achieved in real-world use of edoxaban.